2016
DOI: 10.1080/14656566.2016.1241235
|View full text |Cite
|
Sign up to set email alerts
|

New fixed dose chemical combinations: the way forward for better diabetes type II management?

Abstract: Diabetes type II is a complex disease with unclear pathophysiology. Lack of adherence and high cost of medicines invariably make the management of diabetes type II highly challenging. Newer fixed drug combinations (FDC) are cost effective and can improve the medication adherence thereby prevent the complications of diabetes. Safety and efficacy of newer FDCs are not well established in all populations. Moreover, extrapolating the efficacy and safety data globally may not be pragmatic. Our review will discuss n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Similarly, Raskin et al [36] demonstrated the ability of coupling repaglinide/metformin as an FDC regimen to induce a more rapid decrease in HbA1c levels, as opposed to monotherapy. The present findings are in support of such clinical studies which claim that lower doses of 2 agents in fixed combinations may offer greater efficacy in combination, at the same time reducing the risk of adverse events that may occur with higher doses of monotherapy [37].…”
Section: Fdc As a Measure To Improve Glycaemic Index In T2dm Patientssupporting
confidence: 87%
“…Similarly, Raskin et al [36] demonstrated the ability of coupling repaglinide/metformin as an FDC regimen to induce a more rapid decrease in HbA1c levels, as opposed to monotherapy. The present findings are in support of such clinical studies which claim that lower doses of 2 agents in fixed combinations may offer greater efficacy in combination, at the same time reducing the risk of adverse events that may occur with higher doses of monotherapy [37].…”
Section: Fdc As a Measure To Improve Glycaemic Index In T2dm Patientssupporting
confidence: 87%
“…FDCs are increasingly used in clinical practice for a range of chronic disorders that require the use of multiple treatments, such as chronic obstructive pulmonary disease [22], hypertension [23,24], hepatitis C [25,26], and HIV infection [27,28], with the aim of simplifying treatment regimens and improving clinical outcomes. Similarly, in the field of T2D management, the use of FDCs of effective and well-tolerated therapies can offer a useful treatment option to help optimize therapy for individual patients, and several FDC therapies for T2D are available for clinical use [29].…”
Section: Introductionmentioning
confidence: 99%